Decision Support System for Promotion Assessment using Analytic Hierarchy Process - Kumar, Sanjeev; Gupta, Shivangi (International Journal of Computer Sciences and Engineering, 2025)
Promotion Assessment is an important mechanism in every organization to recognize and utilize the talent of the work force efficiently. Exiting approach uses manual process which is highly subjective in nature and hence has high probability of errors. Therefore, automating this process is required to overcome the deficiencies in the manual process. Decision Support System is the most appropriate tool for automation in such kind of scenarios. The proposed system uses criteria based on profession skill and behavioural aspects of staff. This system can further be used to predict those staffs that need training program/ domain technical skill and also predict those staffs that have higher chances of promotion in next assessment. It is based on multi-criteria ranking procedure utilizing Analytic Hierarchy Process (AHP) and weighted score method. The system can be utilized to improve the credibility of the whole assessment process adding transparency to the system. To test the model, the sample is taken from the Defence lab